2019
DOI: 10.1101/776260
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Young children combine sensory cues with learned information in a statistically efficient manner: But task complexity matters

Abstract: Research Highlights• Young children are sensitive to, and can learn, environmental regularities. Can they also utilize such learned regularities in a statistically efficient manner?• We demonstrate that 6-7-year olds are capable of learning and utilizing regularities in a statistically efficient fashion, and in a manner indistinguishable from adult behavior.• However, variables such as task complexity can influence young children's behavior to a greater extent than that of adults, leading their behavior to loo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 59 publications
(58 reference statements)
0
2
0
Order By: Relevance
“…Also, it has been suggested that "the developing visual system may be optimized for speed and detecting sensory conflicts" (Nardini et al, 2010, p. 17041). Recently, these ideas have been challenged by studies showing near-optimal integration in this age group (Bejjanki et al, 2020;Nava et al, 2020;Negen et al, 2019), and in particular by Rohlf et al (2020), who showed that integration develops prior to cross-sensory recalibration. In the current study, we found that even though perception of tactile stimuli is strongly affected by the presence of a visual cue, the less-dominant modality (touch) still had an effect on the perceived stimulus location.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, it has been suggested that "the developing visual system may be optimized for speed and detecting sensory conflicts" (Nardini et al, 2010, p. 17041). Recently, these ideas have been challenged by studies showing near-optimal integration in this age group (Bejjanki et al, 2020;Nava et al, 2020;Negen et al, 2019), and in particular by Rohlf et al (2020), who showed that integration develops prior to cross-sensory recalibration. In the current study, we found that even though perception of tactile stimuli is strongly affected by the presence of a visual cue, the less-dominant modality (touch) still had an effect on the perceived stimulus location.…”
Section: Discussionmentioning
confidence: 99%
“…Also, it has been suggested that “the developing visual system may be optimized for speed and detecting sensory conflicts” (Nardini et al., 2010 , p. 17041). Recently, these ideas have been challenged by studies showing near‐optimal integration in this age group (Bejjanki et al., 2020 ; Nava et al., 2020 ; Negen et al., 2019 ), and in particular by Rohlf et al. ( 2020 ), who showed that integration develops prior to cross‐sensory recalibration.…”
Section: Discussionmentioning
confidence: 99%